2013
DOI: 10.3892/ijo.2013.2242
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical trial of peptide vaccination with URLC10 and VEGFR1 epitope peptides in patients with advanced gastric cancer

Abstract: Peptide vaccine treatment has attracted attention in recent years as a new therapy option for chemotherapy-resistant, advanced, unresectable cancer. The safety of peptide vaccination with HLA-A*2402-restricted URLC10-A24-177 and VEGFR1-A12-9 1084 epitope peptides (fixed 2-mg dose) was investigated in a phase I clinical trial of patients with advanced gastric cancer who were refractory to chemotherapy. We determined the HLA genotype of the subjects after enrollment, results of which were held by the evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The breaking of immune tolerance against tumor‐associated antigens and induction of autoimmunity against tumors should be a useful approach for the treatment of tumors . Although it is common to consider conventional cytotoxic chemotherapy as an immunosuppressive modality, more recent studies have indicated that some cytotoxic drugs have the ability to disrupt pathways of immune suppression and immune tolerance in a manner that depends on the drug type, its dose, and the treatment schedule in relation to the immune‐based intervention .…”
Section: Discussionmentioning
confidence: 99%
“…The breaking of immune tolerance against tumor‐associated antigens and induction of autoimmunity against tumors should be a useful approach for the treatment of tumors . Although it is common to consider conventional cytotoxic chemotherapy as an immunosuppressive modality, more recent studies have indicated that some cytotoxic drugs have the ability to disrupt pathways of immune suppression and immune tolerance in a manner that depends on the drug type, its dose, and the treatment schedule in relation to the immune‐based intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility studies evaluated vaccination with tumor-specific antigens in gastric cancer patients (123,124). Vaccination was well-tolerated and showed an increase in antitumor immuno-response.…”
Section: Gastric Cancer and Adenocarcinoma Of The Gastroesophageal Jumentioning
confidence: 99%
“…Compared to whole-protein antigens, an epitope-based vaccine may overcome these above-mentioned shortcomings and have many advantages such as increased safety and immunogenicity of vaccine for increased protective potency ( Tang et al, 2015 ). The epitope-based vaccines are on the road to the market, especially in the treatment of cancer ( Higashihara et al, 2014 ; Correale et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%